Diagnosis of NSM FRP reinforcement in concrete by using mixed-effects models and EMI approaches. (1st October 2021) - Perera, Ricardo; Gil, Alberto; Torres, Lluis; Barris, Cristina
Highlights: A new approach for monitoring of RC members strengthened by NSM FRP systems. Use of different types of piezoelectric sensors. Novel method based on the combination of linear mixed methods with EMI results. Filtering of the damage effects, frequency range and uncontrollable phenomena. Verification of the proposed methodology with two experimental beams. Abstract: The use of fibre reinforced polymer (FRP) in civil construction applications with near-surface mounted (NSM) method has gained considerable popularity worldwide as suitable method for strengthening existing concrete structures. However, there is very little experience in the implementation of methods able to give a reliable prediction about the health of this type of structures even although sudden and brittle failure modes are likely to happen. Because of it, more contributions on this topic are really needed in order to prevent possible catastrophic failures. In this paper, a novel approach based on linear mixed effects models implemented on results from experimental tests performed on concrete beams strengthened with NSM FRP has been explored. In spite of their rapid growth in other areas, mixed effects models have barely been applied in structural problems. Impedance measurements captured from PZT sensors embedded and externally bonded to the beam are used for the quantitative and qualitative analysis. This research shows that the evolution of the progressive damage for this kind of repairing method can be effectively monitored using the proposed approach.